SISTEM PRESIDENSIAL PASCA AMANDEMEN UNDANG-UNDANG DASAR 1945; STUDI KASUS KEPEMIMPINAN PRESIDEN SBY DAN JOKOWI - Efriza Efriza (Prima Center Indonesia, 2016)
This article discusses the powers of the President-Parliament based on the leadership of the President SBY and Jokowi, who often get caught up in the tension between agencies as a consequence of a fusion between the presidential system and a multi-party, which allegedly will lead to a deadlock in decision-making to a government crisis but found it does not happen conflict leading up to the crisis of governance as in the era of President Abdurrahman Wahid.Key words: Presidential, President-DPR, President SBY and Jokowi